Long non-coding RNA CHCHD4P4 promotes epithelial-mesenchymal transition and inhibits cell proliferation in calcium oxalate-induced kidney damage - Zhang,C. (2018)
Kidney stone disease is a major cause of chronic renal insufficiency. The role of long non-coding RNAs (lncRNAs) in calcium oxalate-induced kidney damage is unclear. Therefore, we aimed to explore the roles of lncRNAs in glyoxylate-exposed and healthy mouse kidneys using microarray technology and bioinformatics analyses. A total 376 mouse lncRNAs were differentially expressed between the two groups. Using BLAST, 15 lncRNA homologs, including AU015836 and CHCHD4P4, were identified in mice and humans. The AU015836 expression in mice exposed to glyoxylate and the CHCHD4P4 expression in human proximal tubular epithelial (HK-2) cells exposed to calcium oxalate monohydrate were analyzed, and both lncRNAs were found to be upregulated in response to calcium oxalate. To further evaluate the effects of CHCHD4P4 on the cell behavior, we constructed stable CHCHD4P4-overexpressing and CHCHD4P4-knockdown HK-2 cells. The results showed that CHCHD4P4 inhibited cell proliferation and promoted the epithelial-mesenchymal transition in kidney damage and fibrosis caused by calcium oxalate crystallization and deposition. The silencing of CHCHD4P4 reduced the kidney damage and fibrosis and may thus be a potential molecular target for the treatment of kidney stones.